Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1038/sc.1993.39
|View full text |Cite
|
Sign up to set email alerts
|

The role of functional electrical stimulation in the rehabilitation of patients with incomplete spinal cord injury - observed benefits during gait studies

Abstract: The benefits of a functional electrical stimulation (FES) gait programme were assessed in a group of 6 incomplete spinal cord injured subjects. Measurements were made of quadriceps spasticity, lower limb muscle strength, postural stability in standing, spatial and temporal values of gait, physiological cost of gait and independence in activities of daily living. The subjects were assessed before commencement of the programme and after a period of gait training using FES. The benefits derived as a result of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 11 publications
(2 reference statements)
4
73
0
Order By: Relevance
“…Other research centers have shown that lower limb neuroprostheses can improve the short-term therapeutic and functional outcomes of persons with incomplete SCI by demonstrating participants' improvements in step length and maximal walking velocity [17][18][19][20]. This study supplements these data by documenting additional therapeutic and functional gains, such as a greatly improved maximal walking distance, reduced physiological cost, and decreased variability of temporal and spatial gait parameters.…”
Section: Post-implant Gait Parametersupporting
confidence: 56%
See 2 more Smart Citations
“…Other research centers have shown that lower limb neuroprostheses can improve the short-term therapeutic and functional outcomes of persons with incomplete SCI by demonstrating participants' improvements in step length and maximal walking velocity [17][18][19][20]. This study supplements these data by documenting additional therapeutic and functional gains, such as a greatly improved maximal walking distance, reduced physiological cost, and decreased variability of temporal and spatial gait parameters.…”
Section: Post-implant Gait Parametersupporting
confidence: 56%
“…After the neuroprosthesis was implanted and the participant had 12 weeks of training with it, his post-training maximal walking distance increased by 20 Table 2), and this moved him from a nonambulator to a limited independent community ambulator (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The average re-strengthening time was found to be approxi mately 1 month, but there was considerable varia bility.2 In incomplete spinal cord injury patients, strengthening of the quadriceps muscles by the stimula tion and progressive resisted exercise programme with weights at the ankle lasted 6 months and was completed by all subjects. 3 The alternative approach in chronic non-ambulatory hemiparetic patients with immediate walking by FES, which provided their independent gait in 2-3 weeks4,5 excluded any previous strengthening programme. With sometimes much better preserved lower limb muscles due to spasticity and complete support of the upper limbs in paraplegic patients, immediate standing with out previous conditioning was found to be rational and challenged both the research and the patient part of the team.…”
Section: Discussionmentioning
confidence: 99%
“…1 The average re-strengthening time was found to be approximately 1 month.2 In incomplete spinal cord injury patients, the isotonic strengthening was replaced by a progressive resisted quadriceps conditioning by the stimulation and weights attached at the ankle and lasted 6 months. 3 On the other hand, it was demonstrated in chronic non-ambulatory hemiparetic patients that an immedi ate walking with FES without previous strengthening of the muscles could provide gait without the support of an accompanying therapist in 2-3 weeks.4,5 Therefore immediate standing assisted by FES without previous conditioning of the muscles was chosen for paraplegic patients in this study.…”
Section: Introductionmentioning
confidence: 96%